2013
DOI: 10.1038/npp.2013.230
|View full text |Cite|
|
Sign up to set email alerts
|

Repeated Binge-Like Ethanol Drinking Alters Ethanol Drinking Patterns and Depresses Striatal GABAergic Transmission

Abstract: Repeated cycles of binge alcohol drinking and abstinence are key components in the development of dependence. However, the precise behavioral mechanisms underlying binge-like drinking and its consequences on striatal synaptic physiology remain unclear. In the present study, ethanol and water drinking patterns were recorded with high temporal resolution over 6 weeks of binge-like ethanol drinking using the ‘drinking in the dark' (DID) protocol. The bottle exchange occurring at the beginning of each session prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 37 publications
11
107
0
Order By: Relevance
“…While our results specifically describe the effects of EtOH on GABAergic transmission in the DLS, Wilcox et al (2014) report that acute EtOH exposure and chronic EtOH drinking induces a higher frequency of basal miniature IPSC (mIPSC) events in the DMS, and a lower frequency of mIPSC events in the DLS. This DMS to DLS response difference may be explained by the higher expression of FSIs in the DLS (Schlösser et al, 1999;Luk and Sadikot, 2001), as the majority of mIPSCs onto MSNs arise from FSIs (Koos et al, 2004).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…While our results specifically describe the effects of EtOH on GABAergic transmission in the DLS, Wilcox et al (2014) report that acute EtOH exposure and chronic EtOH drinking induces a higher frequency of basal miniature IPSC (mIPSC) events in the DMS, and a lower frequency of mIPSC events in the DLS. This DMS to DLS response difference may be explained by the higher expression of FSIs in the DLS (Schlösser et al, 1999;Luk and Sadikot, 2001), as the majority of mIPSCs onto MSNs arise from FSIs (Koos et al, 2004).…”
Section: Discussionmentioning
confidence: 88%
“…Blomeley et al (2011), as well as Wilcox et al (2014) demonstrated that acute EtOH exposure to striatal slices depresses inhibitory synaptic transmission onto principal medium spiny neurons (MSNs) of the DLS. This acute EtOH effect may persist in chronic drinking models as chronic EtOH consumption in rodents and non-human primates depresses GABA release onto MSNs of the DLS/putamen (Cuzon Carlson et al, 2011;Wilcox et al, 2014). Despite the mounting evidence of EtOHinduced disinhibition of DLS MSNs, the microcircuit and molecular determinants of EtOH-induced MSN disinhibition remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…15 Injured mice exposed to the DID protocol may be demonstrating ''front-loading'' behaviors in which drinking rates have been shown to be maximal within the first 15 min of drinking. 64,67 In this way, TBI could be increasing binge drinking frequency, which could be assessed using shorter limited-access durations.…”
Section: Discussionmentioning
confidence: 99%
“…In cynomolgus monkeys, prolonged 930 intermittent alcohol drinking decreased the frequency of GABA A receptor-mediated miniature IPSCs recorded from the MSNs in the caudoventral area of the putamen (Cuzon Carlson et al, 2011). This area corresponds to the dorsolateral striatum in rodents, and a similar reduction of IPSC frequency was produced by repeated binge drinking in mice in this striatal area, but also in the dorsomedial striatum (Wilcox et al, 2014). These data suggest that heavy, long-term alcohol exposure causes a depression of GABAergic transmission in the dorsal striatum, contributing to an increased output from this structure.…”
Section: Ethanol Administered In Vitro Enhanced Ipsps Andmentioning
confidence: 99%
“…However, alcohol-preferring mice consume enough ethanol to achieve blood ethanol levels exceeding 23 mM (100 mg/dl) in the recently described binge-drinking model ("drinking in the dark") (Rhodes et al, 2005), and the reintroduced intermittent ethanol access model results in escalation of ethanol drinking in rats, with intoxicating blood ethanol levels (Wise, 1973;Simms et al, 2008). Even if induction of alcohol dependence in these binge models is debatable, long-term binge drinking has been shown to produce a variety of neuroadapations Wilcox et al, 2014).…”
Section: +mentioning
confidence: 99%